Jawabanmu

2014-09-04T20:52:36+07:00
 (\sqrt{3})^{-2}+( \sqrt{3})^{-1} + (\sqrt{x})^0+ \sqrt{3}^1+ \sqrt{3} ^2=a+b \sqrt{3}

pasangkan saja mas ...

( \sqrt{3})^{-2} + ( \sqrt{3}  )^2 untuk memudahkan ambil x= \sqrt{3}

maka persamaan
 x^{-2} + x^{2} =(x+ \frac{1}{x} )^2 - 2 . x . \frac{1}{x}  = (x+ \frac{1}{x} )^2-2

totalnya  (x+1/x)² -2 +(x+1/x) +1 = (x+1/x)²+(x+1/x)-1=a+b . x
(x+1/x)(x+1/x+1)-1=a+b.x .... x²+1+x+1+1/x²+1/x-1=a+b.x

3+1+√3+1+1/3+1/√3-1=a+b√3
7/3 +√3+1/√3=a+b√3 kalikan √3 menjad9 (7/3)√3+3+1=a√3+b

dapat disimpulak a=7/3 dan b=4